Social media and the birth of an Islamic social movement: ODOJ (One Day One Juz) in contemporary Indonesia. Issue 134 (2nd January 2018) - Nisa, Eva F.
ABSTRACT: The Indonesian democratic transition, which occurred after the collapse of the New Order, was a significant moment that enabled diverse Islamic groups to use media for their own interests. However, little has been discussed regarding the use of media in dakwah (Islamic proselytising) performed by Muslim activists who are not inclined to participate in radical activities. This article focuses on the use of social media in dakwah by One Day One Juz (ODOJ), which endeavours to encourage Muslims to revive the spirit of reading the Qur'an through the mobile application WhatsApp. Given that ODOJ has successfully recruited more than 140, 000 followers in Indonesia and abroad, this article investigates the key actors of ODOJ and the extent to which it has mobilised religious sentiments among Muslims from diverse affiliations. It argues that WhatsApp has enabled the birth of a semi-virtual Qur'anic movement, which is rooted in the Tarbiyah movement. Unlike well established Islamic movements in Indonesia that harness global computer networks to strengthen their influence, ODOJ has been dependant on technology since its inception. It demonstrates the capacity of technology in generating and crafting this new semi-virtual socio-religious movement. ODOJ has painted new colour onto the contemporary Islamic public and its presence is imperative to understanding the transformation of the religious media-scape in Indonesia.